Mastering social sciences research proposal: a step by step guide - Shafie, Dalili Izni; Milhem, Marwan (Penerbit UiTM (UiTM Press), 2025)
Mastering social sciences research proposal: a step by step guide provides a practical approach to writing research proposals in the social sciences, covering key steps like formulating research questions, designing methodology, and structuring proposals. It’s an essential resource for researchers and students.